No light without the dark: Perspectives and hindrances for translation of cardiac optogenetics. (August 2020) - Richter, Claudia; Bruegmann, Tobias
Abstract: Over the last decade, optogenetic stimulation of the heart and its translational potential for rhythm control attracted more and more interest. Optogenetics allows to stimulate cardiomyocytes expressing the light-gated cation channel Channelrhodopsin 2 (ChR2) with light and thus high spatio-temporal precision. Therefore this new approach can overcome the technical limitations of electrical stimulation. In regard of translational approaches, the prospect of pain-free stimulation, if ChR2 expression is restricted to cardiomyocytes, is especially intriguing and could be highly beneficial for cardioversion and defibrillation. However, there is no light without shadow and cardiac optogenetics has to surmount critical hurdles, namely "how" to inscribe light-sensitivity by expressing ChR2 in a native heart and how to avoid side effects such as possible immune responses against the gene transfer. Furthermore, implantable light devices have to be developed which ensure sufficient illumination in a highly contractile environment. Therefore this article reviews recent advantages in the field of cardiac optogenetics with a special focus on the hindrances for the potential translation of this new approach into clinics and provides an outlook how these have to be carefully investigated and could be solved step by step.